The LATERAL ROOT DENSITY gene regulates root growth during water stress in wheat. Issue 9 (19th February 2020) - Placido, Dante F.; Sandhu, Jaspreet; Sato, Shirley J.; Nersesian, Natalya; Quach, Truyen; Clemente, Thomas E.; Staswick, Paul E.; Walia, Harkamal
Summary: Drought stress is the major limiting factor in agriculture. Wheat, which is the most widely grown crop in the world, is predominantly cultivated in drought‐prone rainfed environments. Since roots play a critical role in water uptake, root response to water limitations is an important component for enhancing wheat adaptation. In an effort to discover novel genetic sources for improving wheat adaptation, we characterized a wheat translocation line with a chromosomal segment from Agropyron elongatum, a wild relative of wheat, which unlike common wheat maintains root growth under limited‐water conditions. By exploring the root transcriptome data, we found that reduced transcript level of LATERAL ROOT DENSITY (LRD) gene under limited water in the Agropyron translocation line confers it the ability to maintain root growth. The Agropyron allele of LRD is down‐regulated in response to water limitation in contrast with the wheat LRD allele, which is up‐regulated by water deficit stress. Suppression of LRD expression in wheat RNAi plants confers the ability to maintain root growth under water limitation. We show that exogenous gibberellic acid (GA) promotes lateral root growth and present evidence for the role of GA in mediating the differential regulation of LRD between the common wheat and the Agropyron alleles under water stress. Suppression of LRD also had a positive pleiotropic effect on grain size and number under optimal growth conditions. Collectively, our findings suggest that LRD can be potentially useful for improving wheat response to water stress and altering yield components.